(untitled) (Eurasian Journal of Philology Science and Education, 2018)
In connection with the process of globalization, cultural and inter-ethnic interactions special meaning is given to «ethnic image». Information from mass media about ethnic groups and ethnic stereotypes widely held by society plays an important role in the formation of an ethnic image. This article examines the question of the perception and reflection of Kazakhs in the linguistic consciousness of foreigners. Associative experiments for proving the veracity of the results and the conclusions of the study are carried out with the help of two films that elicit positive/negative social resonances. They are S. Kozhykov’s film «Kyz Zhibek» (positive) and E. Tursynov’s film «Kelin» (negative). The respondents were foreign students of Al-Farabi Kazakh National University. The article provides statistical data gathered with the help of qualitative and quantitative analyses. These associative experiments reinforce the basic contours of the ethno-stereotypes of «Kazakhs» and other ethnicities.